2013
DOI: 10.1097/paf.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen–Plastic Bag Suicide

Abstract: The use of pure nitrogen gas to commit suicide has recently become more popular, although suicides involving nitrogen oxide fumes have been occasionally reported in the past. The cause of death in such cases is attributed to asphyxia due to forced depletion of oxygen, a subcategory of a phenomenon dubbed environmental hypoxia. A case of a 26-year-old man who committed suicide by inhaling nitrogen through a plastic bag is reported. The exact method of suicide used here is one of the many described in detail on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Nitrogen gas has caused accidental deaths in industrial or laboratory explosion, and during scuba diving and anesthesia (2). Although it is reported that industrial nitrogen asphyxiation hazards resulted in 80 deaths during the period 1992 through 2002, there is a paucity of documentation regarding nitrogen gas as a means of committing suicide (2,3). Nitrogen is a colorless, odorless, nontoxic, and generally inert gas that is a normal component (78.09%) of the atmosphere, at standard temperature and pressure (4).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nitrogen gas has caused accidental deaths in industrial or laboratory explosion, and during scuba diving and anesthesia (2). Although it is reported that industrial nitrogen asphyxiation hazards resulted in 80 deaths during the period 1992 through 2002, there is a paucity of documentation regarding nitrogen gas as a means of committing suicide (2,3). Nitrogen is a colorless, odorless, nontoxic, and generally inert gas that is a normal component (78.09%) of the atmosphere, at standard temperature and pressure (4).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several organizations and internet communities in favor of assisted suicide have promoted the use of nitrogen (N2) gas to that end (2). Nitrogen gas has caused accidental deaths in industrial or laboratory explosion, and during scuba diving and anesthesia (2). Although it is reported that industrial nitrogen asphyxiation hazards resulted in 80 deaths during the period 1992 through 2002, there is a paucity of documentation regarding nitrogen gas as a means of committing suicide (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations